Sensory, Behavioral, And Affective Effects on Engagement and Destination Brand Love: A Platform Study - Conny, Conny; Zaid, Sudirman; Sinarwaty, Sinarwaty; Yusuf, Yusuf; Nur, Nofal (PT. Riset Press International, 2026)
This study aims to analyze the influence of sensory, behavioral, and affective factors on digital engagement and its implications for destination brand love on the digital platform of Wakatobi tourist destinations. In addition, this study also examines the role of digital engagement as a mediating variable in the relationship between sensory, behavioral, and affective to destination brand love. The approach used is quantitative with Structural Equation Modeling analysis techniques based on Partial Least Squares (SEM-PLS). The data was collected through a questionnaire with a five-point Likert scale that was distributed to 160 respondents who were tourists who had accessed Wonderful Wakatobi's Instagram and the Wakatobi Tourism website at least three times. The analysis was carried out through the evaluation of the outer model and the inner model to test the validity, reliability, and significance of the relationship between variables. The results of the study show that sensory, behavioral, and affective have a positive and significant effect on digital engagement, and digital engagement has a significant effect on destination brand love. In addition, digital engagement has been proven to be able to mediate the relationship between sensory, behavioral, and affective to destination brand love. These findings indicate that travelers' sensory experiences, interactive behaviors, and emotional engagement in digital platforms play an important role in increasing digital engagement, ultimately reinforcing a love for destination brands. This research provides theoretical contributions in the development of digital-based destination marketing literature as well as practical implications for destination managers in designing digital content strategies that are more interactive, emotional, and multisensory to increase destination brand love.